Working Principle and Experimental Design of Hydraulic Wind Heating - Wan, Li; Liu, Chengpeng; SANGYONGLAMU; Wang, Wei (International Journal of Electric Power and Energy Studies, 2024)
The wind energy heating system studied in this article mainly consists of three parts: vertical axis wind turbines, heaters, and heat exchange devices. A liquid stirring heating experimental platform was built based on the heating principle. By using a heating experimental platform, the speed of the driving motor is controlled to simulate the input characteristics of the wind turbine under different speed conditions, so that the heater can reach a stable state from static state. Study the changes in temperature and efficiency during the start-up process. Finally, an economic evaluation was conducted on the investment cost throughout the entire lifecycle by comparing it with coal-fired heating and electric heating methods.